Prolonged Walking with a Wearable System Providing Intelligent Auditory Input in People with Parkinson’s Disease - Ginis, Pieter; Heremans, Elke; Ferrari, Alberto; Dockx, Kim; Canning, Colleen G.; Nieuwboer, Alice (Frontiers in Neurology, 2017)
Rhythmic auditory cueing is a well-accepted tool for gait rehabilitation in Parkinson’s disease (PD), which can now be applied in a performance-adapted fashion due to technological advance. This study investigated the immediate differences on gait during a prolonged, 30 minute, walk with performance-adapted (intelligent) auditory cueing and verbal feedback provided by a wearable sensor-based system as alternatives for traditional cueing. Additionally, potential effects on self-perceived fatigue were assessed. Twenty-eight people with PD and thirteen aged-matched healthy elderly (HE) performed four 30 minute walks with a wearable cue and feedback system. In randomized order, participants received: 1) Continuous auditory cueing; 2) Intelligent cueing (10 metronome-beats triggered by a deviating walking rhythm); 3) Intelligent feedback (verbal instructions triggered by a deviating walking rhythm); and 4) No external input. Fatigue was self-scored at rest and after walking during each session. The results showed that while HE were able to maintain cadence for 30 minutes during all conditions, cadence in PD significantly declined without input. With continuous cueing and intelligent feedback people with PD were able to maintain cadence (p=0.04), although they were more physically fatigued than HE. Furthermore, cadence deviated significantly more in people with PD than in HE without input and particularly with intelligent feedback (both: p=0.04). In PD, continuous and intelligent cueing induced significantly less deviations of cadence (p=0.006). Altogether, this suggests that intelligent cueing is a suitable alternative for the continuous mode during prolonged walking in PD, as it induced similar effects on gait without generating levels of fatigue beyond that of HE.